The Middle East and globalization : encounters and horizons - Stetter, Stephan, 1972- (New York, NY : Palgrave Macmillan, 2012)
"The Middle East and Globalizations: Encounters and Horizons brings together contributions by leading scholars in Middle East Studies sharing the interest in theoretically ambitious approaches to globalization and world society. The book discusses past and contemporary political, societal, economic and cultural trends in the Middle East against the background of comprehensive theories of globalization. The contributions to this book draw from a shared methodological approach looking at fractures and horizons of globalization shaping the Middle East"--
Includes bibliographical references (p. [241]-268) and index.
Keywords: Globalization -- Middle East; Globalization -- Africa, North; Geopolitics -- Middle East; Geopolitics -- Africa, North; POLITICAL SCIENCE / Globalization; POLITICAL SCIENCE / International Relations / General; POLITICAL SCIENCE / Economic Conditions; POLITICAL SCIENCE / History & Theory